2018
DOI: 10.1134/s0006297918010030
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of progesterone by the ascomycete Aspergillus niger N402

Abstract: The ability of the ascomycete Aspergillus niger N402 to transform exogenous progesterone was investigated. We found that this strain has steroid-hydroxylating activity and can introduce a hydroxyl group into the progesterone molecule mainly at positions C11(α) and C21 with predominant formation of 21-hydroxyprogesterone (deoxycortone). In addition, formation of 6β,11α-dihydroxyprogesterone was also observed. Studying the effects of the growth medium composition and temperature on progesterone conversion by A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In this study, microbial biotransformation of PCR by A. niger was an- molecule (Savinova, et al, 2018). Another A. niger JMU-TS528 could transform rutin to isoquercitrin (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this study, microbial biotransformation of PCR by A. niger was an- molecule (Savinova, et al, 2018). Another A. niger JMU-TS528 could transform rutin to isoquercitrin (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 68%
“…Other previous reports also have suggested that A. niger has the ability to produce different bioactive compounds by different metabolic pathways, and it can also increase the physiological and biochemical activities of biological substrates by modifying their original molecules. Such as A. niger N402 was reported has steroid‐hydroxylating activity and can introduce a hydroxyl group into the progesterone molecule (Savinova, et al., 2018). Another A. niger JMU‐TS528 could transform rutin to isoquercitrin (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The 11α-hydroxylation is the most frequently reported transformation of progesterone and its derivatives during biotransformation in cultures of filamentous fungi [ 20 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. However, in the vast majority of cases, apart from the 11α-hydroxy derivative, other products were also identified [ 20 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…An analogous cascade course was previously described during the biotransformation of progesterone leading to 6β-hydroxy-11-oxoprogesterone in cultures of Mucor M881 strains [ 51 ] and Isaria farinosa KCh KW1.1 [ 17 , 33 ]. On the other hand, the ability to dihydroxylate progesterone leading to the 6β,11α-dihydroxy derivative was previously observed in cultures of the following strains: Aspergillus nidulans VKPM F-1069 [ 45 ], A. niger N402 [ 43 ], A. ochraceus [ 49 ], Rhizomucor pusillus and Absidia griseolla var. igachii [ 48 ], Rhizomucor tauricus IMI23312 [ 50 ], Cephalosporium aphidicola [ 46 ], and Trichoderma koningii , T. hamatum , T. aureoviride , and T. pseudokoningii [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation